SUPERVISI TENAGA KEPENDIDIKAN DI MADRASAH ALIYAH NEGERI 5 JAKARTA UTARA - ADE KURNIA (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
This study aims to describe: (1) planning for the supervision of education personnel at MAN 5 North Jakarta, (2) implementing the supervision of education personnel at MAN 5 North Jakarta, (3) evaluating the implementation of supervision of education personnel at MAN 5 North Jakarta, (4) follow-up further evaluation results of the implementation of the supervision of education personnel at MAN 5 North Jakarta. This type of research is a qualitative research with an ethnographic research design. The location of this research is MAN 5 North Jakarta. Data collection techniques were carried out by observation, in-depth interviews, and documentation. Data analysis techniques are carried out by grouping and selecting data from research based on the quality of their truth, then describing and concluding the results to answer the existing problems. The results of this research are planning activities including: (1) formulation of legal basis, objectives, and indicators, (2) preparation of supervision program carried out by the internal supervision team, (3) setting targets and schedules for supervision of education personnel, (4) determining approaches and the technique used, and (5) the selection and determination of the instrument. The supervision instrument is in accordance with the main tasks and functions of each educational staff. Implementation activities include (1) presentation of performance results focused on instrument components, (2) observation of physical evidence carried out by visits, (3) confirming and asking for explanations of performance results, (4) recording the results of supervision that has been carried out in the form of reports. results of supervision, (5) submitting the results of supervision notes. The evaluation activities include (1) the head of the madrasah obtaining basic considerations about the implementation of supervision, (2) the head of the madrasa knowing the implementation of effective supervision in improving performance, (3) the head of the madrasa knowing the difficulties and obstacles experienced by education staff. Follow-up activities include: (1) making improvement programs, (2) general coaching as a form of improvement programs, (3) implementing improvement programs with in-house training and inviting resource persons from outside the madrasa. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan: (1) perencanaan supervisi tenaga kependidikan di MAN 5 Jakarta Utara, (2) pelaksanaan supervisi tenaga kependidikan di MAN 5 Jakarta Utara, (3) evaluasi pelaksanaan supervisi tenaga kependidikan di MAN 5 Jakarta Utara, (4) tindak lanjut hasil evaluasi pelaksanaan supervisi tenaga kependidikan di MAN 5 Jakarta Utara. Jenis penelitian ini adalah penelitian kualitatif dengan desain penelitian etnografi. Lokasi penelitian ini di MAN 5 Jakarta Utara. Teknik pengumpulan data dilakukan dengan pengamatan, wawancara mendalam, dan dokumentasi. Teknik analisis data dilakukan dengan mengelompokkan dan menyeleksi data dari penelitian berdasarkan kualitas kebenarannya, kemudian menggambarkan dan menyimpulkan hasilnya untuk menjawab permasalahan yang ada. Hasil penelitian ini adalah pada kegiatan perencanaan meliputi: (1) perumusan landasan hukum, tujuan, dan indikator, (2) penyusunan program supervisi yang dilakukan tim supervisi internal, (3) penetapan sasaran dan jadwal supervisi tenaga kependidikan, (4) penetapan pendekatan dan teknik yang digunakan, dan (5) pemilihan dan penetapan instrumen. Instrumen supervisi sesuai dengan tugas pokok dan fungsi masing-masing tenaga kependidikan. Pada kegiatan pelaksanaan meliputi (1) pemaparan hasil kinerja difokuskan pada komponen instrumen, (2) pengamatan bukti fisik yang dilakukan dengan kunjungan, (3) melakukan konfirmasi dan meminta penjelasan hasil kinerja, (4) melakukan pencatatan hasil supervisi yang telah dilaksanakan dalam bentuk laporan hasil supervisi, (5) menyampaikan hasil catatan supervisi. Pada kegiatan evaluasi meliputi (1) kepala madrasah memperoleh dasar pertimbangan tentang pelaksanaan supervisi, (2) kepala madrasah mengetahui pelaksanaan supervisi yang efektif dalam meningkatkan kinerja, (3) kepala madrasah mengetahui kesulitan dan hambatan yang dialami tenaga kependidikan. Pada kegiatan tindak lanjut meliputi: (1) membuat program perbaikan, (2) pembinaan umum sebagai bentuk program perbaikan, (3) melaksanakan program perbaikan dengan in house training dan mengundang narasumber dari luar madrasah.